Efektivitas Model Pembelajaran Kooperatif Think Pair Share (TPS) Terhadap Hasil Belajar Matematika - Trias Fitriana Sari (SNHRP, 2022)
Cooperative Learning Model Type Think Pair Share (TPS), is a learning model that can be used to determine the effectiveness of math story problems. This research was conducted with the aim of knowing the effectiveness of the cooperative learning model of Think Pair Share (TPS) on the Learning Outcomes of 5th Grade Math Story Problems at SDN Sumur Welut III/440 Surabaya. This type of research is a quantitative research using a Quasi Experimental research design in the form of Nonequivalent Control Group Design with Pretest Posttest Control Group Design. The population in this study were all 5th grade students of SDN Sumur Welut III/440 Surabaya, totaling 46 students with a sample consisting of 24 students in class II A as the experimental class and 31 students in class II C as the experimental class. Data were collected through a written test consisting of 10 multiple choice questions. The results of this study indicate that there is an Effectiveness of the Think Pair Share (TPS) cooperative learning model on Learning Outcomes of Math Story Problems for Grade 5 Students at SDN Sumur Welut III/440 Surabaya.